Stosowanie zrównoważonej karty wyników w controllingu strategicznym - Pewniak-Kaliska, Olga (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main purpose of a paper is to present the Balanced Scored Card. The article shows the characteristic features the BSC which determine using its in strategic controlling. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 326-331